FIELD TEST STUDY ON WIND TURBINE PERFORMANCE HORIZONTAL AXIS THREE SPIRAL BLADES RELATED TO SOLIDITY NUMBER EFFECTS - Yudi Wantoso; Abdul Hamid (Universitas Mercu Buana, 2026)
Abstract—The use of electrical energy in Indonesia is currently very high, but the energy used is still dominated by fossil energy, even though the potentials for alternative energy in Indonesia is very large and cannot be utilized properly, one of which is wind energy. Wind power plant are renewable power plants where the use of renewable energy is expected to be able to replace energy sourced from fossils which are limited in number. This research was conducted using a three-blade spiral horizontal axis wind turbine (TASH) related to the effect of solidity number with the aim of knowing the performance of TASH with a diameter of 1.536 m. The method used is this study is a field test at the Tanjung Pasir beach, Tangerang Regency, Banten. TASH performance is assessed by measured parameters such as voltage value, generator output current and torque value; also, non-dimensional parameters such as power coefficient, torque coefficient, CT, and the value of Tip Speed Ratio, TSR, generated due to TASH rotation at each wind speed from 1 m/s to 6 m/s. Field test results obtained. Experimental actual power = 9.991 watts, torque value = 6.0 Nm (wind speed 5 m/s), Power coefficient, CP = 0.066 and Torque coefficient, CT = 0.674 at 2.0 m/s wind speed, Solidity number = 0.976